Research of neutron interaction with matter under high density interaction. Part I. Cross section of the neutron interaction with matter under high density interaction - Yu. G. Shchepkin; V. I. Slisenko; E. A. Pavlenko; T. A. Kostyuk (Ядерна фізика та енергетика)
Neutrons interaction with matter under high density interactions (DI) was considered. It was shown that un-der neutron cross section measurement with high DI and production as result of interaction neutrons with matter of the second states with great value of such parameters as neutrons cross section, yield and life time probabil-ity of the interaction neutron with matter depends on DI and considered parameters. The expressions, related neutrons transmission, cross section and change of the neutrons transmission through the samples pair from different matters, which simultaneously placed on neutron beam, under the change of neutrons transmission sequence through them (transmission asymmetry) with DI and considered parameters of the second states were obtained. Method for revelation for the cross section change under DI change and improved experimental in-stallation were described.